Acute and chronic neuropsychiatric symptoms in novel coronavirus disease 2019 (COVID-19) patients: A qualitative review - Calen J. Smith; Calen J. Smith; Perry Renshaw; Perry Renshaw; Perry Renshaw; Deborah Yurgelun-Todd; Deborah Yurgelun-Todd; Deborah Yurgelun-Todd; Chandni Sheth; Chandni Sheth (Frontiers in Public Health, 2022)
The coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was declared a global pandemic by the World Health Organization (WHO) on March 11th, 2020. It has had unprecedented adverse effects on healthcare systems, economies, and societies globally. SARS-CoV-2 is not only a threat to physical health but has also been shown to have a severe impact on neuropsychiatric health. Many studies and case reports across countries have demonstrated insomnia, depressed mood, anxiety, post-traumatic stress disorder (PTSD), and cognitive change in COVID-19 patients during the acute phase of the infection, as well as in apparently recovered COVID-19 patients. The goal of this narrative review is to synthesize and summarize the emerging literature detailing the neuropsychiatric manifestations of COVID-19 with special emphasis on the long-term implications of COVID-19.